Prevalence and incidence rates of cardiovascular, autoimmune, and other diseases in patients with psoriatic or psoriatic arthritis: a retrospective study using Clinical Practice Research Datalink. (28th October 2014) - Edson‐Heredia, E.; Zhu, B.; Lefevre, C.; Wang, M.; Barrett, A.; Bushe, C.J.; Cox, A.; Wu, J.J.; Maeda‐Chubachi, T.
Abstract: Background: Previous studies have demonstrated that patients with psoriasis have higher rates of comorbidities compared to the general population. Despite the clinical and economic burden of psoriatic disease, there have been few large‐scale observational studies focused on this condition. Objective: To assess rates of cardiovascular, autoimmune, infectious and other conditions in patients with psoriasis or psoriatic arthritis (PSA). Methods: The data for this retrospective study were obtained from the Clinical Practice Research Datalink (CRPD). Cohorts of patients with psoriasis ( n  = 27 672; mild, n  = 22 174, severe, n  = 5498) and PSA ( n  = 1952) were generated based on the diagnosis made by general practitioner or specialist recorded in CPRD between 2006 and 2010. Frequencies of comorbidities at baseline and incidence rate ratios (IRR) of medical conditions occurring during follow‐up were calculated and compared between groups. Cox proportional hazard models were employed to compare hazard ratios (HR) of comorbidities across the same subpopulations previously described. Results: Significant differences in the unadjusted risk of cardiovascular disease, hyperlipidaemia, diabetes, skin cancer and autoimmune diseases were observed between patients with differing severity of psoriasis or between PSA and psoriasis patients. The adjusted HR analyses confirmed patients with severe psoriasis had significantly higher rates of several conditions including diabetes (1.23; 95% CI: 1.01–1.51) and rheumatoid arthritis (2.88; 95% CI: 2.25–3.67) compared to patients with mild psoriasis. Patients with PSA had significantly higher adjusted rates of hypertension (1.30; 95% CI: 1.01–1.68), rheumatoid arthritis (6.93; 95% CI: 5.45–8.80) and ankylosing spondylitis (6.98; 95% CI: 2.37–20.58) compared to those with severe psoriasis. Conclusion: Patients with mild psoriasis are less affected by comorbid conditions than those with severe psoriasis, and patients with psoriasis are less affected by comorbidities than those with PSA. Given the differences observed across severities of psoriasis and between psoriasis and PSA, each patient subgroup should be taken into consideration in clinical practice and future research.